2000
DOI: 10.1208/pt010431
|View full text |Cite
|
Sign up to set email alerts
|

Novel mathematical method for quantitative expression of deviation from the Higuchi model

Abstract: A simple mathematical method to express the deviation in release profile of a test product following Higuchi's kinetics from an ideal Higuchi release profile was developed. The method is based on calculation of area under the curve (AUC) by using the trapezoidal rule. The precision of prediction depends on the number of data points. The method is exemplified for 2 dosage forms (tablets of diltiazem HCl and microspheres of diclofenac sodium) that are designed to release the drug over a 12-hour period. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…Although the indirect assessment offered by the film hardness study suggests that the rate of water uptake, K eq H 2 O, is tunable in the thiol-ene hydrolyzing networks by changing the molecular functionality of the constituents, no direct rate of hydrolysis is measured. A well-known kinetic model exists for the quantitative comparison among polymer networks used for the controlled-release/drug-delivery applications of pharmaceuticals [25]. The theoretical model, referred to as the Higuchi model, accounts for the relative water permeability of the networks and the concentrations, solubility, and diffusion of agents in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Although the indirect assessment offered by the film hardness study suggests that the rate of water uptake, K eq H 2 O, is tunable in the thiol-ene hydrolyzing networks by changing the molecular functionality of the constituents, no direct rate of hydrolysis is measured. A well-known kinetic model exists for the quantitative comparison among polymer networks used for the controlled-release/drug-delivery applications of pharmaceuticals [25]. The theoretical model, referred to as the Higuchi model, accounts for the relative water permeability of the networks and the concentrations, solubility, and diffusion of agents in the network.…”
Section: Resultsmentioning
confidence: 99%
“…20 The predicted percent of cumulative drug released (CDR) versus square root of time was considered as the reference line. The average absolute difference between AUCs (AADA) in 12 hr system for residual was calculated by using equation 12. Where n is the difference between two successive sampling points, t 100 is the time to 100% drug release and α is the percent deviation.…”
Section: Mathematical Approachmentioning
confidence: 99%
“…Regression analysis was adopted to compute the constants. Gohel et al proposed a mathematical approach for the determination of deviation in Higuchi release profile (17). The rationale behind this study was to select an optimized batch by evaluating the deviation of dissolution data using an AUC-based mathematical approach as well as goodness of fit to the kinetic models.…”
Section: N a Relatively Short Time Helicobacter Pylori (H Pylori)mentioning
confidence: 99%
“…A novel approach of deviation from Highchi model proposed by Gohel et al (17) was used to evaluate deviation between predicted and observed dissolution profile of floating formulations. The predicted percentage CDR at each time point was back-calculated using the regression equation of Higuchi model.…”
Section: Mathematical Approachmentioning
confidence: 99%